2008
DOI: 10.1074/jbc.m709638200
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Transthyretin Tetramer Stability by Cysteine 10 Adducts and the Drug Diflunisal

Abstract: Transthyretin (TTR) is normally a stable plasma protein.However, in cases of familial TTR-related amyloidosis and senile systemic amyloidosis (SSA), TTR is deposited as amyloid fibrils, leading to organ dysfunction and possibly death. The mechanism by which TTR undergoes the transition from stable, soluble precursor to insoluble amyloid fibril and the factors that promote this process are largely undetermined. Most models involve the dissociation of the native TTR tetramer as the initial step. It is largely ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 47 publications
6
48
0
Order By: Relevance
“…These modified subunits integrate into the homo- and hetero-tetramers that comprise the 8 tetramer peaks observed by our UPLC assay. These modifications are in agreement with what has been seen before for TTR and other FLAG-tagged proteins (Kingsbury et al, 2008; Schmidt et al, 2012; Zhang and Kelly, 2003). While these modifications could have modest effects on TTR stability (Kingsbury et al, 2008; Schneider et al, 2001; Zhang and Kelly, 2003), these modifications are not predicted to globally impact the stability of secreted TTR tetramers.…”
Section: Resultssupporting
confidence: 92%
“…These modified subunits integrate into the homo- and hetero-tetramers that comprise the 8 tetramer peaks observed by our UPLC assay. These modifications are in agreement with what has been seen before for TTR and other FLAG-tagged proteins (Kingsbury et al, 2008; Schmidt et al, 2012; Zhang and Kelly, 2003). While these modifications could have modest effects on TTR stability (Kingsbury et al, 2008; Schneider et al, 2001; Zhang and Kelly, 2003), these modifications are not predicted to globally impact the stability of secreted TTR tetramers.…”
Section: Resultssupporting
confidence: 92%
“…44 The drugs diflunisal and tafamidis stabilize the tetramer in vitro and in vivo and are in clinical testing for ATTR. 45,46 In Portugal and Japan, Val30Met ATTR can present as polyneuropathy in patients 20 to 40 years old, leading to disability and early death unless treated with orthotopic liver transplantation. 47 In blacks, Val122Ile ATTR often presents in the sixth or seventh decade with progressive heart failure and/or neuropathy but not with proteinuria, although glomerulosclerosis can mimic AL renal involvement.…”
Section: Commentsmentioning
confidence: 99%
“…Hence, the altered aggregation propensity of the S-sulfonated TTR could in this case not be ascribed solely to the sulfonation (44). Instead, several studies have identified that S-sulfonation of WT and V30M TTR increases the stability of the tetrameric form by providing additional intramonomeric contacts and in this manner prevents amyloid formation (41,45,46). This raises the possibility that increased S-sulfonation of Cys10, for example, through the dietary supplementation of sulfites, may have a protective effect against TTR amyloidosis (47).…”
Section: Cysteine Modifications Have Differential Effects On Ttr Aggrmentioning
confidence: 92%
“…Although it was reported that the presence of mixed disulfides predominantly affects the aggregation propensity of monomeric TTR at mildly acidic pH (39), analytical ultracentrifugation experiments have shown that S-cysteinylation also enhances tetramer dissociation at physiological pH (41). The heterogeneous oxidative modifications produced by carbonylation of TTR destabilize its monomeric form and interfere with the binding of tetramer-stabilizing compounds (42).…”
Section: Cysteine Modifications Have Differential Effects On Ttr Aggrmentioning
confidence: 98%